What Works and What's Safe in Pediatric Emergency Procedural Sedation: An Overview of Reviews. (24th April 2016) - Hartling, Lisa; Milne, Andrea; Foisy, Michelle; Lang, Eddy S.; Sinclair, Douglas; Klassen, Terry P.; Evered, Lisa
Abstract: Background: Sedation is increasingly used to facilitate procedures on children in emergency departments (EDs). This overview of systematic reviews (SRs) examines the safety and efficacy of sedative agents commonly used for procedural sedation in children in the ED or similar settings. Methods: We followed standard SR methods: comprehensive search; dual study selection, quality assessment, data extraction. We included SRs of children (1 month to 18 years) where the indication for sedation was procedure‐related and performed in the ED. Results: Fourteen SRs were included (210 primary studies). The most data were available for propofol (six reviews/50, 472 sedations) followed by ketamine (7/8, 238), nitrous oxide (5/8, 220), and midazolam (4/4, 978). Inconsistent conclusions for propofol were reported across six reviews. Half concluded that propofol was sufficiently safe; three reviews noted a higher occurrence of adverse events, particularly respiratory depression (upper estimate 1.1%; 5.4% for hypotension requiring intervention). Efficacy of propofol was considered in four reviews and found adequate in three. Five reviews found ketamine to be efficacious and seven reviews showed it to be safe. All five reviews of nitrous oxide concluded it is safe (0.1% incidence of respiratory events); most found it effective in cooperative children. Four reviews of midazolam made varying recommendations. To be effective, midazolam should be combined with another agent that increases the risk of adverse events (upper estimate 9.1% for desaturation, 0.1% for hypotension requiring intervention). Conclusions: This comprehensive examination of an extensive body of literature shows consistent safety and efficacy for nitrous oxide and ketamine, with very rare significant adverse events for propofol. There was considerable heterogeneity in outcomes and reporting across studies and previous reviews. Standardized outcome sets and reporting should be encouraged to facilitate evidence‐based recommendations for care.